Introduction to modern instrumentation : for hydraulics and environmental sciences - Guaraglia, Dardo Oscar; Pousa, Jorge Lorenzo (De Gruyter Open, 2014)
A great variety of new instruments based on electronics are used by professionals in environmental research. The technological changes that have occurred in the last few decades have not yet been reflected in academic literature, and this new instrumentation remains somewhat unknown to its possible users. This book attempts to make clear some characteristics of environmental instruments to those uninitiated in the use of electronic instruments.